2017
DOI: 10.3390/su9081422
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hydroelectric Dam Development and Resettlement on the Natural and Social Capital of Rural Livelihoods in Bo Hon Village in Central Vietnam

Abstract: Abstract:The study examined the natural and social capital of Bo Hon villagers in central Vietnam, before and after resettlement within Binh Thanh commune due to the building of Binh Dien Hydroelectric dam on the Huu Trach River. (1) Background: The two-fold aim was to develop solutions to the impacts of resettlement on natural and social capital, and strategies for timely intervention and new livelihoods after households were resettled. (2) Methods: Livelihood survey of all 46 households was conducted in 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 19 publications
3
17
0
1
Order By: Relevance
“…Social assets remained in the models of the entire area and the service support area, exerting a significant impact on farmer income in both cases, which is consistent with the results of most previous studies [45,61,62,65,68,[81][82][83]. However, social assets had no significant impact on the income of residents in the core attraction area and secondary service support area, which is in line with the view of Myroniuk that "social assets do not necessarily affect income" [65].…”
Section: Discussionsupporting
confidence: 88%
“…Social assets remained in the models of the entire area and the service support area, exerting a significant impact on farmer income in both cases, which is consistent with the results of most previous studies [45,61,62,65,68,[81][82][83]. However, social assets had no significant impact on the income of residents in the core attraction area and secondary service support area, which is in line with the view of Myroniuk that "social assets do not necessarily affect income" [65].…”
Section: Discussionsupporting
confidence: 88%
“…The impact of reduces water flow into the Saskatchewan River Delta is a large reduction in the community's ability to trap animals and hunt, all traditional activities and local food sources. The findings align with an international study completed by Nguyen et al, [41], which reveals that dams have substantial impacts on the natural environment, namely, reduced downstream sediment deposition, impaired fish migration, reduced and altered timing of river flow, and flooded upland reservoir areas with associated impacts.…”
Section: Land Stewardshipsupporting
confidence: 89%
“…Natural capital in our paper is measured at the household level and defined the natural capital as cultivated land and forest land. NGUYEN et al (2017) demonstrated that the more cultivated land the household have the more possible returns the household can get in a village in central Vietnam. Generally, more cultivated land the household have means they can allocate more land for plantation of economics plants to earn more returns than planting rice, and less likely to immerse in poverty (HUANG et al, 2006).China is a country with very complicated terrain with geographical features characterized by mountains, hills, plateaus, and deserts, and the cultivated land is distributed unevenly over the country.…”
Section: Natural Capital and Income Inequalitymentioning
confidence: 99%